( 3 7 ) −2+1 ÷ ( 3 7 ) −1 = [(

Question

(

3

7

)

−2+1

÷ (

3

7

)

−1

= [(

3

7

)

−1

]

−7​

in progress 0
Julia 1 month 2021-08-12T15:18:00+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-12T15:19:49+00:00

    Sorry I am unable to understand

    0
    2021-08-12T15:19:52+00:00

    Answer:

    (37) - 2 + 1 \div (37) - 1 = ((37) - 1) - 7

     = 36 \div 36 = 36 - 7 \\  = 1  | = |  35

    hence LHS is not equal to RHS

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )